A Comprehensive Analysis of METTL1 to Immunity and Stemness in Pan-Cancer - Gao, Zijie; Xu, Jianye; Zhang, Zongpu; Fan, Yang; Xue, Hao; Guo, Xing; Deng, Lin; Wang, Shaobo; Zhao, Rongrong; Zhang, Ping; Li, Gang (Frontiers in Immunology, 2022)
Background Previous studies have reported the effect of N7-methylguanosine (m7G) regulator methyltransferase like-1 protein (METTL1) in tumor initiation, metastasis, and chemosensitivity. However, the relationship between METTL1 and cancer immune infiltration is not validated and the prognostic significance of METTL1 in pan-cancer remains unclear. Methods Clinical parameters, including gender, age, lifetime, stage, and treatment response were analyzed to evaluate the prognostic significance of METTL1. To evaluate protein level of METTL1, the METTL1 activity was generated by single sample gene set enrichment analysis. The one-class logistic regression algorithm was used to calculate the stemness indices based on transcriptomics and methylation data of pan-cancer and pluripotent stem cells. The relationship between METTL1 expression or activity and tumor immune infiltration were analyzed to explore the significance of METTL1 in tumor immunotherapy. Meanwhile, the correlation between three immunotherapeutic biomarkers and METTL1 was investigated. Finally, to calculate the association between drug sensitivity and METTL1 expression, spearman correlation analysis was performed. Results METTL1 was not intimately related to gender, age, tumor stage, or treatment outcome of the various cancers, but it displayed potential prognostic significance for evaluating patient survival. High METTL1 expression was related to tumor progression-relevant pathways. Moreover, METTL1 exhibited a distinct correlation with tumor immune microenvironment infiltration and stemness indices. In the anti-PD-L1 cohort, patients in treatment response group exhibited significantly higher METTL1 expression than those in the no/limited response group. Further analysis showed that tumor cell lines with higher METTL1 expression were more sensitive to drugs targeting chromatin histone methylation, ERK-MAPK and WNT signaling pathways. Conclusion This study provides insight into the correlation of METTL1 with tumor immune infiltration and stemness in pan-cancer, revealing the significance of METTL1 for cancer progression and guiding more effective and generalized therapy strategies.